Nutritional Stability and Sensory Quality of Fish Chips Made from Recovered Thai Pangas (Pangasianodon hypophthalmus) Mince During Extended Storage: Changes in the Nutritional Parameters of Fish Chips - Hossain, Ismail; Fatema Hoque Shikha; Umme Habiba Sweety; Nafis Tasneem Binti; Mst Prianka Jahan; Muhammad Mehedi Hasan (Fishery Technology, 2024)
This study aimed to develop chips from (Thai pangas (Pangasianodon hypophthalmus) fish filleting discards  and evaluate their nutritional stability during storage at 28-32°C. The chips were made with 40% recovered mince, 22.5% rice bran, and 20% mashed potatoes. Nutritional parameters, including moisture, protein, lipid, ash, carbohydrates, and calories, were monitored initially at 15-day intervals, then every 30 days. Results showed minimal changes in sensory qualities over a period of 270 days. The findings indicate that fish chips made from recovered Thai pangas mince can be stored at room temperature for up to nine months without significant degradation in nutritional aspects/parameters.